Malaria chemoprophylaxis, birth weight and child survival. - Greenwood, A; Armstrong, JR; Byass, P; Snow, R; Greenwood, B (1992)
Study of the effects of malaria chemoprophylaxis given during pregnancy on birthweight and investigation of the influence of birthweight on child survival suggest that, in a rural area of The Gambia, chemoprophylaxis given during pregnancy might reduce infant mortality by about one-fifth in the children of primigravidae but by less than 5% in the children of multigravidae. In malaria endemic areas, primigravidae should be protected against malaria not only for their own sake but also for that of their infants.